Conceptions of Knowledge Creation, Knowledge and Knowing A Phenomenography of Singapore Chinese Language Teachers - Tan, Yuh Huann; Tan, Seng Chee.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This book responds to calls for further advancing knowledge creation in schools. It examines sixteen Chinese Language teachers from Singapore, since language teachers are primarily responsible for the basic literacy that is the foundation of students$1 (Blifelong learning. Positing that people$1 (Bs cultural beliefs and the language(s) they use are inseparable, the book argues that Chinese language teachers possess a unique understanding of the various phenomena that reflect the influences of Chinese culture by virtue of the language they speak and teach. For the purposes of the investigation, it employs phenomenography $1 (Ba methodology aimed at finding and systematising how people interpret the world around them $1 (Bto determine and describe Chinese language teachers$1 (Bconceptions of these phenomena.s
Chapter 1. Why a Study on Teachers$1 (BConception of Knowledge Creation -- Chapter 2. Understanding Knowledge Creation -- Chapter 3. Understanding Personal Epistemology -- Chapter 4. Designing the Phenomenographic Study and Constituting the Outcome Spaces -- Chapter 5. Teachers$1 (BConceptions of Knowledge and Knowing -- Chapter 6. Teachers$1 (BConceptions on the Phenomenon of Knowledge Creation in General -- Chapter 7. Teachers$1 (BConceptions on the Phenomenon of Knowledge Creation in Education -- Chapter 8. Discussions on Teachers$1 (BConceptions on the Phenomena of Knowledge, Knowing, and Knowledge Creation -- Chapter 9. Conclusions -- Appendix A: Interview Questions and the Translations in Chinese -- Appendix B: A Simple Transcription Scheme.s
Keywords: Language and education; Language and languages$1 (BStudy and teaching.s; Teaching; Language Education; Language Teaching; Teaching and Teacher Education